2018
DOI: 10.1016/j.neuroimage.2018.05.025
|View full text |Cite
|
Sign up to set email alerts
|

The neural basis of free language choice in bilingual speakers: Disentangling language choice and language execution

Abstract: For everyday communication, bilingual speakers need to face the complex task of rapidly choosing the most appropriate language given the context, maintaining this choice over the current communicative act, and shielding lexical selection from competing alternatives from non-target languages. Yet, speech production of bilinguals is typically flawless and fluent. Most of the studies available to date constrain speakers' language choice by cueing the target language and conflate language choice with language use.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…Indeed, even with equal behavioural performances, the changes in activation in anticipated ROI showed that different brain strategies are actually being used for a similar result. This type of result has also been reported in other bilingual studies (e.g., Ansaldo et al, 2015; Reverberi et al, 2018). Measures of brain activity could be even more valuable in situations such as that encountered here, in which the processing of stimuli does not lead to differences in performance in spite of differences in language proficiency/formational level and age.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, even with equal behavioural performances, the changes in activation in anticipated ROI showed that different brain strategies are actually being used for a similar result. This type of result has also been reported in other bilingual studies (e.g., Ansaldo et al, 2015; Reverberi et al, 2018). Measures of brain activity could be even more valuable in situations such as that encountered here, in which the processing of stimuli does not lead to differences in performance in spite of differences in language proficiency/formational level and age.…”
Section: Discussionsupporting
confidence: 88%
“…These results extended previous research by the same group [51] that had also shown cost-free switching when participants named each picture consistently in the same language (reflecting bottom-up availability of the label) as opposed to choosing one language or the other randomly for each picture to ensure they were using both languages equally as frequently, as required by the experimenters (see also [52], their Experiment 1, Figure 2 showing lack of switch costs for voluntary switching in balanced bilinguals). Other experiments where participants also chose freely which language to use replicated reduced behavioral switch costs and distinct engagement of dlPFC (dorsolateral prefrontal cortex) and SMA/ACC during voluntary switching as compared to forced switching [53], (see also [54], although it remains to be corroborated whether activation in the striatal and cerebellar regions, which are also integral to language control, show similar reductions).…”
Section: Glossarymentioning
confidence: 89%
“…Studies that consequently let bilingual participants voluntarily switch between their languages in the lab have in some cases observed switch costs comparable to traditional switch costs observed in cued language-switching paradigms, but in other cases found reduced switch costs or even no switch costs at all (Blanco-Elorrieta & Pylkkänen, 2017;De Bruin et al, 2018;Gollan & Ferreira, 2009;Gollan, Kleinman, & Wierenga, 2014;Gross & Kaushanskaya, 2015;Jevtović, Duñabeitia, & de Bruin, 2019;Kleinman & Gollan, 2016;Reverberi et al, 2018). Findings on voluntary language switching may generalize mostly to dual language contexts in which language task schemas are not in competition (Green & Abutalebi, 2013;Heredia & Altarriba, 2001).…”
Section: Ecological Validity Of Research Findings On Bilingual Languamentioning
confidence: 98%